Launching a pre-sessional course of english for foreign applicants to national technical university "Kharkiv polytechnic institute”: challenges and outcomes - Lazareva, Olga; Kovtun, Olena (Національний технічний університет "Харківський політехнічний інститут", 2021)
The article discusses a strategy of development of the pre-sessional English course for foreign students of the Faculty of International education of National Technical University “Kharkiv Polytechnic Institute” (NTU “KhPI”). Challenges for foreigners studying at Ukrainian HEIs in English are analyzed. The results of the language needs analysis of foreign applicants with insufficient language background as well as EMI teachers’ estimation of the corresponding aspects of the students’ knowledge are provided. The course syllabus was designed, and, based on the two-year experience of its implementation, conclusions on specific aspects of teaching English to foreigners in the Ukrainian environment are made.

В статті розглянуто стратегію створення курсу з англійської мови для іноземних студентів підготовчого відділення Національного технічного університету “Харківський політехнічний інститут” (НТУ “ХПІ”). Проаналізовано проблемні питання навчання іноземців в українських вишах англійською мовою. Надано результати аналізу мовних потреб вступників-іноземців з недостатньою мовною підготовкою, а також оцінка викладачами спеціальних предметів відповідних аспектів знань студентів. Розроблено робочу навчальну програму курсу, та, на основі дворічного досвіду її впровадження, зроблено висновки про особливості викладання англійської мови іноземцям в україномовному середовищі.
Впровадження на підготовчому відділенні курсу з англійської мови для іноземних вступників до Національного технічного університету “Харківський політехнічний інститут”: виклики та здобутки
Keywords: syllabus design; needs analysis; розробка робочої навчальної програми; аналіз потреб